Applying critical systems thinking to social prescribing: a relational model of stakeholder "buy-in" - Alison Fixsen; Helen Seers; Marie Polley; Jo Robins (BMC, 2020)
Abstract Background Social prescribing (SP) allows health professionals to refer primary care patients toward health and wellbeing interventions and activities in the local community. Now widely implemented across the UK and adopted in other nations, questions arise concerning the modelling of present and future schemes, including challenges to full engagement encountered by stakeholders, which lie beyond the scope of traditional evaluations. Critical Systems Thinking (CST) allows for holistic analysis of fields where multiple stakeholders hold diverse interests and unequal power. Methods We use CST to (a) critically examine a developing rural social prescribing scheme from multiple stakeholder perspectives and (b) present a relational model for local social prescribing schemes. Our fieldwork included 24 in-depth interviews, regular planning meetings with key stakeholders, and discussions with those involved with national and international SP landscaping. A modified grounded theory approach was used for the analysis, and to consider the core elements of social prescribing sustainability. Results Our study confirms that local social prescribing schemes must operate with numerous stakeholder interests in mind, seeking to address real life social complexity and offer integrated solutions to multifaceted issues. Three main areas are discussed: holistic vision and boundary judgments; barriers and facilitators; relational issues and "emotional buy in". Problems for staff include selecting suitable clients, feedback and technological issues and funding and evaluation pressures. Barriers for clients include health, transport and expense issues, also lack of prior information and GP involvement. Emotional "buy-in" emerged as essential for all stakeholders, but hard to sustain. Based on our findings we propose a positive relational model comprising shared vision, confidence and commitment; motivation and encouragement, support and wellbeing focus, collaborative relationships, communication and feedback, access to information /resources, learning in and from action, with emotional "buy-in" at its heart. Conclusion Those implementing social prescribing in different localities inevitably face hard choices about what and whom to include. Research on the sustainability of social prescribing remains limited, studies are required to ascertain which "holistic" models of social prescribing work best for which communities, who are the main beneficiaries of these approaches and how "buy-in" is best sustained.